(untitled) (Anclajes, 2017)
This article analyzes representations of the intellectual that appeared in essays and conferences of Ricardo Rojas. In these works, the author defines himself as an interpreter of miscegenation, willing to travel, in symbolic terms, to the historical past and toward a collective unconscious to recover the deep meanings that exist in folklore. It also analyzes the way that interchanges with Peruvians Luis Varcárcel and Uriel García, among others, allows one to see the existence of strong ties of intellectual solidarity, the free flow of ideas, and the joint formation of archeological and photographical archives of the indigenous world. Rojas’ dialogue with these Peruvian intellectuals results in a mutual regionalist legitimation, including a positive Americanization –and a symbolic indigenization– of Argentina.